PELAKSANAAN TUPOKSI BADAN LINGKUNGAN HIDUP KABUPATEN KAMPAR TERHADAP DAERAH ALIRAN SUNGAI TAHUN 2013 - Andy Ansyari; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Environment Agency Kampar district is formed through Government Regulation No. 06 of 2008 concerning the organizational structure and working procedures of the area, where local regulations Kampar district number 28 of 2009 on licensing and services business recommendations and / or environmental activities. With regard to environmental sustainability, in Law No. 32 of 2004 on Regional Governance in the 22K article described in organizing autonomous region has an obligation to preserve the environment , so that the existence of the Environment Agency is able to realize the Kampar District Environmental Protection and Management of Quality in the Context of Sustainable Development Environmental Support.In this study the authors use the theory proposed by R. Terry (2004:7) there are four things that a basic principle in management, namely planning, organizing, actuating and controlling. The method that I use in this study is the reduction method, namely the collection of field data from various sources and then processed into ingredients in the explanation/description of the problems studied. Description, namely the exposure results of research conducted in the field in the form of matter, phenomena and concrete data. Conclusion, ie withdrawal of a general viewpoint based on issues that have been presented . From the results of research on the implementation of the duties of the Environment Agency on the Kampar river basin in 2013 is not consistent with the goals and targets set, this is caused by the ability of employees, lack of financial support from local governments, and the lack of adequate facilities and infrastructure at the Environment Agency life Kampar district, resulting in maximal execution of duties and functions of the Environment Agency Kampar district.Keyword : BLH, TUPOKSI, Organisasi dan Manajemen